The Image in Discussion: For a Theory of the Image to its Credit of the Invisible - Díez Álvarez, José Javier (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2020)
We analyze the value of the scopic drive in the ambivalent action of seeing: extromission and intromission. Emphasizing that the implicit screen of our images is revealed by our vision in the confrontation with the real, as modern historiography teaches from its theories and devices of seeing and representation, verifying that confrontation by the triumph of trompe l'oeil and the simulation. The complexity of the technical productive story of the images reflects the artificiality arguing both objectivity and effusion of image, scientific connivance as a phantom, from anamorphism to mechanical devices as significant historical turns.